Combinação de técnicas fenotípicas para distinguir Candida albicans de Candida dubliniensis e uma investigação dos mecanismos de resistência a derivados azólicos em isolados de Candida albicans de origem animal - Bandeira, Silviane Praciano (2017)
Azole-resistant Candida albicans have been described in human clinical practice and in strains of veterinary origin. The objective of this study was to reevaluate laboratory identification of azole-resistantC. albicansfrom veterinary isolates, proposing a combination of phenotypic methods for the reliable identification of the species. In addition, this studyaimed to investigate the resistance mechanisms of the strains. Thirty-seven veterinary strains of azole-resistant C. albicansand three human strains of C. dubliniensis were submitted to phenotypic identification by germ tube test, micromorphological analysis oncornmeal agar, growth on chromogenic agar, growth on sunflower seed agar, opacification test onTween 80™ agar and PCR. For study of resistance mechanisms, C. albicansstrains were evaluated for efflux of6G rhodamine (n=11), determination of ergosterol content (n=6) and expression of CDR1, CDR2, MDR1 and ERG11 genes (n=30). All studied strains presented positive germ tube test and production of chlamydoconidia on cornmeal agar. Thirty five strains (35/37) showed green colonies on chromogenic agar. On sunflower seed agar, 36 strains (36/37) presented a smooth colony pattern, and on Tween 80™ agar, 34 (34/37) had opacification in less than 5 days. All strains tested showed specific product on PCR, which confirmed their identity as C. albicans.C. dubliniensis strains showed green colonies on ChromoAgar Candida™, a rough appearance on sunflower agar, did not form opacification zone on Tween80™agar, after up to 12 days, and did not present specific products in PCR.In resistance studies, azole resistant strains showed higher relative fluorescence unit difference values than sensitive isolates in efflux of6G rhodamine tests, thus demonstrating increased activity of efflux pumps. There was no significant difference in ergosterol content. It was verified that 73.3% (22/30) of the isolates presented overexpression of one or more genes, of which 40.9%, 18.2%, 59.1% and 54.5% strains overexpressedCDR1, CDR2, MDR1 and ERG11, respectively. No isolate overexpressed simultaneously the four genes. Finally, we conclude that the combination of phenotypic techniques leads to reliable differentiation of C. albicansandC. dubliniensis, reserving molecular techniques for more specific contexts. Resistance mechanisms to azole derivatives ofthe studied strains is multifactorial, including, at a minimum, the enhanced activity of efflux pump activity and the gene overexpression.